Strategic Issues in Managing Photovoltaic Business in the Context of the European Union. Case Study-Romania - Tanţău, Adrian Dumitru; Nichifor, Maria Alexandra; Regneală, Horaţiu (International Journal of Economic Practices and Theories, 2014)
Global demand on renewable sources of energy is increasing more than ever. Apart from the high level of pollution, the diminishing levels of traditional sources of energy, such as coal and gas, are determining a new shift towards the integration of renewable energy in the traditional systems for the purpose of a sustainable way of existence in all member states of the European Union. The PV industry has been the main source of installed renewable energy in the European Union for the last two years, representing an important subject of political discussions and scientific conferences due to its future development potential. However, these debates have only inquired aspects regarding financial results or the capacity of the solar industry, leaving the field of the actual practiced business models of the PV companies unexplored and thus, worthy of our attention. The current paper aims to research the current and future business models of PV companies and the effects of strategic issues in the PV field on these business models. By using theDelphimethod, based on questionnaires and interviews with experts in the field, this study reveals the expected evolution of PV business models depending on the permanent changes of the external environment, which has been a significant source of influence for the solar energy producers in the last three years. The relevance of this study lies in the interdependence of PV business models and the external environment, which has been a main source of concern for companies in the field in every member state of the European Union and that is inquired in the present paper in the case study of Romania.